Modulating Room-Temperature Phosphorescence-To-Phosphorescence Mechanochromism by Halogen Exchange - Takewaki, Yoshika; Ogawa, Takuji; Tani, Yosuke (Frontiers in Chemistry, 2022)
Modulating the stimulus-responsiveness of a luminescent crystal is challenging owing to the complex interdependent nature of its controlling factors, such as molecular structure, molecular conformation, crystal packing, optical properties, and amorphization behavior. Herein, we demonstrate a halogen-exchange approach that disentangles this problem, thereby realizing the modulation of room-temperature phosphorescence-to-phosphorescence mechanochromism. Replacing the bromine atoms in a brominated thienyl diketone with chlorine atoms afforded isostructural crystals; i.e., molecules with different halogen atoms exhibited the same molecular conformation and crystal packing. Consequently, amorphization behavior toward mechanical stimulation was also the same, and the phosphorescence of amorphous states originated from the same conformer of each diketone. In contrast, the phosphorescence properties of each conformer were modulated differently, which is ascribable to heavy atom effects, resulting in the modulation of the mechanochromism. Thus, halogen exchange is a promising approach for modulating the stimulus-responsive photofunctions of crystals involving spin-forbidden processes.